A graphical approximation to generalization: Definitions and diagrams - Fernando Martel García; Leonard Wantchekon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The fundamental problem of external validity is not to generalize from one experiment, so much as to experimentally test generalizable theories. That is, theories that explain the systematic variation of causal effects across contexts. Here we show how the graphical language of causal diagrams can be used in this endeavour. Specifically we show how generalization is a causal problem, how a causal approach is more robust than a purely predictive one, and how causal diagrams can be adapted to convey partial parametric information about interactions.
Keywords: B0; C1; C18; C99; 330; generalized causal inference; external validity; causal diagrams; policy experiments; non-parametric methods; econometric methodology